Exploring two-dimensional graphene and boron-nitride as potential nanocarriers for cytarabine and clofarabine anti-cancer drugs. (October 2020) - Saravanan, Vinnarasi; Rajamani, Akilan; Subramani, Mohanapriya; Ramasamy, Shankar
Graphical abstract: Highlights: The PG and h-BN sheets are used as a drug carriers. The PG sheet has more interaction energy with CYT and CLF drug than h-BN sheet. Adsorption energies of CYT and CLF on PG are -24.29 kcal/mol & -23.31 kcal/mol. Results shows, PG sheet has therapeutic potential as a drug delivery vehicle. Abstract: Development in two-dimensional (2D) drug-delivery materials have quickly translated into biological and pharmacological fields. In this present work, pristine graphene (PG) and hexagonal boron nitride (h-BN) sheets are explored as a drug carrier for cytarabine (CYT) and clofarabine (CLF) anti-cancer drugs using density functional theory (DFT). The obtained geometrical, energetic and electronic properties revealed that the PG sheet is more reactive and it adsorbs CYT and CLF anti-cancer drugs better than the h-BN sheet. The adsorption energies of CYT and CLF on PG sheet is -24.293 and -23.308 kcal/mol respectively, this is due to the delocalized electrons present in the PG sheet. The flow of electron direction between anti-cancer drugs and 2D sheet are calculated by ΔN, ΔEA(B), and ΔEB(A) parameters and Natural bond orbital analysis (NBO). The electronic and optical properties are calculated to understand the chemical reactivity and stability of the complex systems. The obtained results exhibit that the PG sheet retains significant therapeutic potential as a drug delivery vehicle for a drug molecule to treat cancer therapy.